2021
DOI: 10.1136/bmjmilitary-2021-001846
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and suicidal ideation in US military veterans with histories of COVID-19 infection

Abstract: IntroductionThere have been reports of increased prevalence in psychiatric conditions in non-veteran survivors of COVID-19. To date, however, no known study has examined the prevalence, risk and protective factors of psychiatric conditions among US military veterans who survived COVID-19.MethodsData were analysed from the 2019 to 2020 National Health and Resilience in Veterans Study, which surveyed a nationally representative, prospective cohort of 3078 US veterans. Prepandemic and 1-year peripandemic risk and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 24 publications
3
27
1
Order By: Relevance
“…Being around others who are ill or who die from COVID-19 may also have a psychological impact that could confer risk. This appears to have been observed, for example, by Na et al, 22 who found a higher risk of suicidal/self-harm thoughts in people with SARS-CoV-2 who lived with someone who was also infected.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Being around others who are ill or who die from COVID-19 may also have a psychological impact that could confer risk. This appears to have been observed, for example, by Na et al, 22 who found a higher risk of suicidal/self-harm thoughts in people with SARS-CoV-2 who lived with someone who was also infected.…”
Section: Discussionsupporting
confidence: 60%
“…One used a cross-sectional design with 3,078 veterans of whom 233 reported a diagnosis of COVID-19. 22 It found a higher proportion of those with SARS-CoV-2 who reported recent thoughts (12.0% vs. 7.6%; PR 1.58, 1.09–2.29). This study also examined correlates of recent suicidal/self-harm thoughts in those with SARS-CoV-2.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Notably, suicide risk might be elevated in infected subjects with a history of SI. As demonstrated in a study of US veterans, those who were infected with SARS-CoV2 were more likely to exhibit peri-pandemic SI, whose strongest independent predictive factors include the existence of this neuropsychiatric symptom before the pandemic ( Na et al, 2021 ).…”
Section: Hyperinflammation As An Etiological Contributor To Increased...mentioning
confidence: 99%
“…The following brief pet ownership-related questionnaire were added in Wave 2 and embedded among questions regarding mental health outcomes cf. 40 .…”
Section: Page 3/18mentioning
confidence: 99%